Friction and Adhesion of Polysaccharides - Rowena Crockett (Japanese Society of Tribologists, 2014)
This paper provides a brief overview of investigations that have been carried out on the tribological properties of polysaccharides. Much of the work into long chain carbohydrates focuses on adhesion due to the propensity of these molecules to form hydrogen bonds. Polysaccharides play an important role in bioadhesion, but are also used in the mining industry to assist in the separation of minerals. Despite the high adhesion associated with polysaccharides, investigations showing that they can be used to achieve low friction have also been reported.In order to observe an effect on the friction between sliding surfaces in the boundary regime, the polysaccharide must first adsorb onto the surface. Although hydrogen bonding is the dominant interaction for polysaccharides, they can also interact through hydrophobic interactions in aqueous solution, providing the structure of the carbohydrate allows this. Many polysaccharides are charged and can, therefore, be adsorbed onto charged surfaces via electrostatic interactions. If the sliding contact is symmetric, that is both surfaces are of the same material, then it could be expected that bridging between the surfaces would occur due to the same interactions being formed on both sides. However, friction studies have been carried out that show that this phenomenon does not necessarily lead to high friction coefficients.